Educação especial e políticas públicas: construindo narrativas sob a perspectiva dos estudos culturais - Marcia Capellini (2021)
This text consists of research on the implementation of a Special Education policy in the city of Anastácio/Mato Grosso do Sul, Brazil, from the perspective of Cultural Studies. The locus is the municipal education network of the city of Anastácio, located 139 km from Campo Grande, the capital of the state of Mato Grosso do Sul. Students with disabilities, pervasive developmental disorders, their parents/tutors, teachers, and managers of the school units in which they were regularly enrolled participated in the project. An exploratory-descriptive and narrative research was carried out to obtain the data, in a cross-sectional study. There was an absence of a policy and a protocol for attending students with disabilities in the aforementioned education network. One of the hypotheses is that existing policies are reformulated under the logic of those who do not see people with disabilities as subjects who are constituted under historical, political, economic and, above all, cultural conditions. Thus, the main objective is to analyze how the process of implementing a policy takes place through the construction of narratives together with the voices of the protagonists from the perspective of Cultural Studies and what impact it has on the learning process of these students, subjects marked by difference and socially disqualified. Of the authors invited to the dialogue, Said contributed his concept of Orientalism, as well as Marcone's construction of disability - the invention of disability through normality, to analyze the constructions that become true around the theme and reflect negatively on actions in the way of teaching. The final results prove the need to include these voices in educational proposals as a whole, but not only restricting the drafting of normative documents that provide continuity in the policy of hegemony, but a change in actions on teaching issues, so that needs are addressed to the promotion of quality of life and not just to strengthen the school curriculum. Two achievements were the creation of the Special Education Center through Decree No. 698 and the publication of the Deliberation of the CME/Anastácio No. 31, which provides school education for people with disabilities, pervasive developmental disorders and high and abilities or giftedness in the Municipal System of teaching in Anastácio/MS. Keywords: Public Policy, Special Education, Cultural Studies.